Moral distress in correctional nurses: A national survey. (February 2020) - Lazzari, Tiziano; Terzoni, Stefano; Destrebecq, Anne; Meani, Luca; Bonetti, Loris; Ferrara, Paolo
Background: Moral distress is an increasingly documented problem in nursing and might foster nurses' intention to leave their workplace. It has been studied in different settings, but no specific research has been conducted in Italian correctional facilities. A recent Italian study produced a preliminary validation of the Moral Distress Scale for Correctional Nurses, which needs to be completed. Objectives: To investigate the level of moral distress of nurses working in the Italian correctional setting, by completing the validation process of the Moral Distress Scale for Correctional Nurses. Methodology: Multicenter questionnaire survey. All correctional nurses (461) affiliated with the Italian Society of Medicine and Penitentiary Health (also called "Simspe-onlus") were invited to participate and 238 responded. The survey was conducted between April and November 2017 through SurveyMonkey ® . Analysis of covariance was conducted to investigate the relationship between moral distress and the other variables under study. Exploratory factor analysis was conducted on the scale to confirm its dimensions. Ethical considerations: The study was approved by the Italian Society of Medicine and Penitentiary Health (Simspe-onlus). The questionnaire included informed consent, pursuant to the law in force. The software could not accept questionnaires without explicit consent. Data were analyzed anonymously. Findings: The median score was 46.5, indicating moderate moral distress. The only variable affecting moral distress was work experience in correctional facilities. Longer experience was correlated to higher levels of moral distress and intention to leave. Incompetent colleagues and short staffing were related to higher levels of moral distress. The scale confirmed the one-dimensional structure suggested by the original authors. Discussion: This is the first study investigating moral distress among Correctional Nurses. The prison context is a high-risk environment for nurses, increasing the intention to leave the workplace. Conclusion: Corrective and protective measures, such as specific education, are needed to prevent moral distress development and to reduce nurses' shortage in this area.